2008
DOI: 10.1088/0952-4746/28/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the UK domestic radon Action Level to prevent more lung cancers—is it cost-effective?

Abstract: Case studies have shown that radon gas can accumulate within domestic properties at sufficiently high levels that it can cause lung cancer, and recent studies have suggested that this risk remains significant below the UK domestic Action Level of 200 Bq m(-3). Raised radon levels can be reduced by engineering measures, and it has been shown that domestic radon remediation programmes in UK Affected Areas can result in reduced risks to the population and can be cost-effective. We consider here the benefits and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While lowering the action level would avert more lung cancers, our analysis shows that this becomes less cost-effective as the action level is reduced. 40 Similarly, protecting all new homes is more expensive and far less cost-effective than a targeted approach. 13 On the other hand, other researchers suggest that, because smoking cessation programmes are generally more cost-effective than radon remediation programmes, radon remediation programmes should be dropped 41 or reduced, 38,42 and smoking cessation programmes enhanced instead.…”
Section: Discussionmentioning
confidence: 99%
“…While lowering the action level would avert more lung cancers, our analysis shows that this becomes less cost-effective as the action level is reduced. 40 Similarly, protecting all new homes is more expensive and far less cost-effective than a targeted approach. 13 On the other hand, other researchers suggest that, because smoking cessation programmes are generally more cost-effective than radon remediation programmes, radon remediation programmes should be dropped 41 or reduced, 38,42 and smoking cessation programmes enhanced instead.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Sir I am distressed to read in the March issue of this journal [1] a sentence that states, "Case studies have shown that radon gas can accumulate within domestic properties at sufficiently high levels that it can cause lung cancer." (my emphasis).…”
Section: Causes Of Cancermentioning
confidence: 99%